Cultural Change for Aspiration Adaptation: Role of NGO’s in Rural Bangladesh - Abu Hena Reza (Journal of Social and Development Sciences, 2011)
The cultural values in a society affects aspiration window and aspiration adaptation of people belong to that society. The socially transmitted behavioural pattern, the culture, plays important role towards socio-economic changes in the households and country. The changes in culture may be autonomous of exogenously affected. The social organisations like NGOs may act as external agents of changes in culture of a society to initiate aspiration adaptation among the poor. This paper evaluates ability of NGOs to change traditional values to employment, education, healthcare, and women empowerment. Analysing data from a household field survey in rural area of Bangladesh it has been observed that NGOs have ability to change traditional cultural values slowly and partially. The NGOs are successful to reduce poverty and to change approach to healthcare of traditional society. They could not show enough success in raising educational level. NGOs achieved some successes in women empowerment by motivating educated women to work more in earned activities, and by reducing deprivation of women in healthcare. In general, the paper observed that NGOs are able to change culture of a society that may enhance capability of people and may ensure socio-economic development of households in rural areas of Bangladesh to some extent. Hence, NGOs are agents of cultural change in society to create new aspiration windows and aspiration adaptation.